Development of E-Learning System Using Codeigniter Framework and Prototype Model on MTs Negeri 1 Musi Banyuasin - Firamon Syakti; Hutrianto Hutrianto (Journal of Information System and Informatics, 2022)
Based on the 1945 Law, article 31 paragraph one states that every citizen has the right to be taught. So that every educational institution is obliged to provide services under any conditions, including in emergencies such as Covid-19. One solution to overcome this problem is to develop all learning media such as e-learning. With the existence of learning media through e-learning, it is hoped that the learning process will continue to run normally. The problem as mentioned certainly occurs in MTs. Negeri Bumiayu is one of the schools in Musi Banyuasin Regency. To achieve the goal to overcome these problems, namely developing e-learning using the Codeigniter framework and Prototyope model. The results of the development show that the e-learning produced has features that can overcome the learning process well as evidenced by e-learning features such as materials and tasks in the learning process.